We have the system of equations:
![\begin{gathered} (x)/(6)+(y)/(4)=6 \\ (5x)/(6)-(y)/(3)=11 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/im4wckkwpgq199e2v2hb6rxe1dsgm7o1j9.png)
We can solve it by elimination: we will multiply the first equation by 5 and substract from the second equation. Then, we will eliminate x and we can solve for y.
We can write this as:
![\begin{gathered} ((5)/(6)x-(1)/(3)y)-5((1)/(6)x+(1)/(4)y)=11-5(6) \\ (5)/(6)x-(1)/(3)y-(5)/(6)x-(5)/(4)y=11-30 \\ 0x-((1)/(3)+(5)/(4))y=-19 \\ -((4+15)/(12))y=-19 \\ (19)/(12)y=19 \\ y=19\cdot(12)/(19) \\ y=12 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/uxqi519et3yx54at4e2szqh0i6u533a91e.png)
Now, with the value of y, we can solve for x as:
![\begin{gathered} (1)/(6)x+(1)/(4)y=6 \\ (1)/(6)x+(1)/(4)\cdot12=6 \\ (1)/(6)x+3=6 \\ (1)/(6)x=6-3 \\ (1)/(6)x=3 \\ x=3\cdot6 \\ x=18 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/bnx180q4lr3pzexvy292245m6zazzf44f9.png)
Answer: x=18 and y=12